A Poetic Transplant: When Olga Orozco Sings in the Guaraní Language (Letras, 2025)
This article analyzes Susy Delgado’s Guaraní translations of the first two poems by Olga Orozco, included in her book Orozco pytukue (2020). Drawing on comparative literature and translation studies, it examines the strategies applied to the poems “Esos pequeños seres” and “Las muertes”. The results highlight sustained use of paraphrase, neologisms, and syntactic circumlocution that enrich Guaraní’s expressive repertoire. While both domestication and foreignization coexist, foreignization clearly predominates, reinforcing the otherness of the original and confronting readers with cultural difference. The study concludes that Delgado’s work constitutes a glottopolitical act of resistance against Paraguay’s diglossic situation, legitimizing Guaraní as a language of high literature and consolidating its creative potential in poetry.
Keywords: Olga Orozco; Susy Delgado; Poetic Translation; Guarani; Foreignization; Domestication